The Effect of Spiritual Intelligence and Social Competency with the Performance of SMP Teachers in Sinaboi District, Rokan Hilir Regency - Rosyidawati Rosyidawati; Fadly Azhar; Sri Kartikowati (Universitas Riau, 2022)
This study aims to describe the influence of Spiritual Intelligence and Social Competence partially and jointly on the performance of junior high school teachers in Sinaboi District, Rokan Hilir Regency. There are still teachers who are less responsible in carrying out their duties and often leave teaching hours to complete personal interests and are indifferent to their duties, and there are teachers who are not able to complete the tasks given to them properly such as not being picket and other additional tasks. This type of research is descriptive quantitative research. The data collection technique used a questionnaire from 55 teachers. The research method was carried out, namely the respondents gave responses to the questionnaire in the form of a Likert scale. Analysis of the data used descriptive and inferential statistics. The magnitude of the influence generated by spiritual intelligence on teacher performance is 62.7%. The result shows that spiritual intelligence has a significant effect on teacher performance, which is accepTable. The magnitude of the effect produced by social competence on teacher performance is 65.1%. The magnitude of the effect produced by spiritual intelligence and social competence together on teacher performance is 69%. It can be stated that spiritual intelligence and social competence have a significant effect on accepTable teacher performance.